An Analysis of Social Interaction of Autism in Life, Animated Film - Dian Luthfiyati; Abdul Kholiq; Nur Dian Tamimih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The aims of this study were to find social interaction of autism in Life, Animated film. The autistic child in this film is the second son of Suskind Family. This study the writer uses descriptive analysis techniques. The data of this study are the conversation of Life, Animated film. Data analysis techniques used in this study is transcription, classification and analysis. Data source was Life, Animated Film. This study only focused on social interaction. The result of the research shows that Owen was confused and did not understand what people said, he was often smiling by himself, he also often gritting his teeth, he imitated word or sentence that had said by other people, not only sentence but he also imitates several scenes in Disney movie, closed with his mother, he prefers to have relation with older or adult than in age-mates, he shows his disappointment if he left by his friend and he expressed his feeling and what he wanted using different Disney movies. This study shows that autistic children want to be around people, but they are sometimes do not know how to connect with others. The conclusion from this study is supported by family, therapist and people around autism people, becomes important thing to realize their potential of autism. Keywords: social interaction, uutism, life, animated film